2019
DOI: 10.1212/nxi.0000000000000563
|View full text |Cite|
|
Sign up to set email alerts
|

α4-integrin deficiency in B cells does not affect disease in a T-cell–mediated EAE disease model

Abstract: ObjectiveThe goal of this study was to investigate the role of CD 19+ B cells within the brain and spinal cord during CNS autoimmunity in a peptide-induced, primarily T-cell–mediated experimental autoimmune encephalomyelitis (EAE) model of MS. We hypothesized that CD19+ B cells outside the CNS drive inflammation in EAE.MethodsWe generated CD19.Cre+/− α4-integrinfl/fl mice. EAE was induced by active immunization with myelin oligodendrocyte glycoprotein peptide (MOGp35-55). Multiparameter flow cytometry was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Cells from lymph nodes and spleen were isolated by pressing through a 70-µm nylon mesh cell retainer as described previously ( 8 10 ). Cells were treated with red blood cell (RBC) lysis buffer (Sigma-Aldrich), washed twice with cold PBS, and resuspended in PBS for counting by hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…Cells from lymph nodes and spleen were isolated by pressing through a 70-µm nylon mesh cell retainer as described previously ( 8 10 ). Cells were treated with red blood cell (RBC) lysis buffer (Sigma-Aldrich), washed twice with cold PBS, and resuspended in PBS for counting by hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…In support of potential skin-resident B cells are recent studies demonstrating non-recirculatory spleen-resident T-bet hi B cells (Johnson et al, 2020). Several studies reported that IL-10 + Bregs exert their function by acting in secondary lymphoid organs (Hussain et al, 2019, Matsushita et al, 2008, and constitutive lack of α4β1integrin in B cells has been linked to a reduction of IL-10 + Bregs in spleen and exacerbated CNS inflammation in experimental autoimmune encephalitis (Glatigny et al, 2016). However, in our study, increased inflammation in both CHS-like and psoriasiform skin inflammation was paralleled by a decrease in cutaneous IL-10 + Breg numbers and a concomitant increase of their counterparts in spleen.…”
Section: Short-term Deletion Of α4β1-integrin In B Cells Does Not Affmentioning
confidence: 99%
“…Cells from lymph nodes and spleen were isolated by pressing through a 70 µm nylon mesh cell retainer as described [8][9][10] . Cells were treated with red blood cell (RBC) lysis buffer (Sigma-Aldrich, St. Louis, MO, USA), washed twice with cold phosphate buffered saline (PBS), and re-suspended in PBS for counting by hemocytometer.…”
Section: Isolation Of Lymph Node Cells and Splenocytesmentioning
confidence: 99%